A rare case of amyopathic juvenile dermatomyositis associated with psoriasis successfully treated with ustekinumab (2017)
Coexistence between two or more immunological-mediated diseases implies a clinical and therapeutic challenge that is uncommon in the clinical field. We report a rare case of a young patient with amyopathic juvenile dermatomyositis and erythrodermic psoriasis, with an excellent response to ustekinumab.